Interest of Public Health Science Students of State University of Malang to Work in Remote Areas, Borders, and Islands - Adi, Sapto; Mawarni, Dian; Fauzia, Dita Ratna (Preventia: The Indonesian Journal of Public Health, 2023)
The health workforce distribution in Indonesia still needs to be balanced, especially in border areas and islands (DTPK), with no exception for public healthcare workers. This study aimed to determine the interest of public health science students in working in remote areas and the factors associated with the interest of public health science students to work in remote areas. This study design was cross-sectional, and a total sampling method was used. The subjects were final-year students majoring in Public Health Science at the State University of Malang. The dependent variable was the interest of public health science students to work in remote areas. Independent variables included personal input, background environment, and student self-efficacy. Data were analyzed univariate and bivariate using Goodman and Kruskal Tau tests. The result showed that from 79 respondents, 44.3 percent of students were interested in working in remote areas, and 5.1 percent had high self-efficacy to work in remote areas. The factor related to student interest in working in remote areas is the self-efficacy variable (p is 0.000). Most students are not interested in working in rural areas, and self-efficacy is associated with student interest in working in rural areas.